The Role of Financial Technology in Improving Performance in Jordanian Islamic Banks - Hendawi, Raed; Ineizeh, Nehad Ibrahim; Hussein, Obada Jebreen; Alkahtani, Mohammad (Journal of Ecohumanism, 2024)
This study aims to determine how financial technology (FinTech) affects Jordanian Islamic bank's performance. 130 employees of Jordanian Islamic banks made up the study sample. To assess FinTech, which includes automated payment methods, financial inclusion, and automation all of them were considered independent variables, whereas, performance improvement in Jordanian Islamic banks was the dependent variable. The results of the linear regression analysis used to test the hypotheses showed that FinTech has a positive impact and a significant impact on financial performance in Jordanian Islamic banks, with automation having a positive effect of 77%, alternative payment methods having a significant impact of 68%, and financial inclusion having a positive impact of 65%. Future research should, according to the study, take into account more factors to more thoroughly evaluate how FinTech has improved performance in Jordanian Islamic banks. Additionally, future research can broaden the sample size, strengthening the validity of the findings.